A comparative study on antioxidant status combined with integrated biomarker response in Carassius auratus fish exposed to nine phthalates. Issue 10 (11th March 2014) - Qu, Ruijuan; Feng, Mingbao; Sun, Ping; Wang, Zunyao
ABSTRACT Laboratory experiments were performed to determine the antioxidant responses to nine phthalates (PAEs) in the liver of the goldfish Carassius auratus. The fish were injected with 10 mg/kg body weight of each PAE for 1 day and 4, 8, and 15 days. The potential biotoxicity of the PAEs were examined using the antioxidase and lipid peroxide indices. We determined that the superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and malondialdehyde (MDA) levels displayed different trends following prolonged treatment, suggesting that metabolism generated either less toxic or more active substances. Based on the intensity of enzymes inhibition, MDA content, and the calculated integrated biomarker response (IBR), the toxicity order was determined as follows: dibutyl phthalate (DBP) > diethyl phthalate (DEP) > diisodecyl phthalate (DIDP) > diphenyl phthalate (DPP) > butyl benzyl phthalate (BBP) > diallyl phthalate (DAP) > dicyclohexyl phthalate (DCHP) > dimethyl phthalate (DMP) > di(2‐ethylhexyl) phthalate (DEHP). In particular, DBP, which exhibited significant inhibition of enzyme activity and the greatest decrease in MDA content, may be a highly toxic contaminant. Furthermore, our results suggest that the IBR may be a general marker of pollution. © 2014 Wiley Periodicals, Inc. Environ Toxicol 30: 1125–1134, 2015.